INFLUENCE OF CITATION PRACTICES ON ACADEMIC ASSESSMENT - Horacio Rivera (Central Asian Journal of Medical Hypotheses and Ethics, 2022)
In writing scientific papers, proper citation and referencing are crucial and thereby should be taught to graduate students and novice researchers as tools for counteracting the pervasive errors in citing, quoting, and referencing. Although the relevance of citation counts and derived indicators such as the h-index in assessing research performance is out of question, this emphasis has resulted in an “impact or perish” culture featuring post-production misrepresentation and related misbehaviors. Herein, I appraise the use of citations in academic assessment, citations in original vs. review articles, convenience and country of origin biases, and some related issues. The current landscape highlights that formal instruction on citation practices and their implications should be included in graduate programs and enduringly reinforced by mentors in laboratories.